Quantification of indocyanine-green-enhanced fluorescence with spectrophotometry (O2C®) in low anterior rectal resection: a prospective study - Darwich, Ibrahim; Demirel-Darwich, S.; Weiß, Christel; Willeke, F. (Techniques in coloproctology, 2025)
Introduction: Despite spectacular visuals and the seemingly convincing rationale of using indocyanine-green-enhanced fluorescence in assessing bowel perfusion during colorectal resections, a lingering sense of subjectivity remains in the challenge of quantifying this fluorescence. This prospective study analyzed the application of O2C® spectrophotometry to quantify zones of fluorescence on the large bowel during low anterior resection. Materials and methods: Patients receiving a low anterior resection for cancer of the mid- and lower rectum were enrolled in this observational prospective study between February 2020 and December 2022. O2C® blood-flow measurement was performed at three different zones of fluorescence intensity (optimal [O], sufficient [S], and absent [A]), visualized at the designated and already skeletonized site of colon transection. The primary end point was to assess whether the O2C® flow value exceeds 164 arbitrary units (AU) at the zone of optimal fluorescence. The secondary objective was to assess whether there were statistically significant differences in flow parameters between the three zones, thus confirming reproducibility of measurements. Results: A total of 40 patients were enrolled in this study. Of these, 38 patients remained for statistical analysis with regard to O2C® measurement of the fluorescence zones. The O2C® flow parameter measured at the zone of optimal fluorescence was greater than 164 AU in all cases (100%, p < 0.0001). There were statistically significant differences in flow parameters measured at the three different zones of fluorescence (O-S: p < 0.0001; O-A: p < 0.0001; S-A: p = 0.0023). Conclusion: This study proves the feasibility and reproducibility of quantifying zones of indocyanine green (ICG)-enhanced fluorescence on the bowel. All O2C® flow measurements that were collected at the zone of optimal fluorescence exceeded 164 AU, thereby adding more evidence to this value as a suggested cut-off parameter in terms of bowel perfusion.
Online veröffentlicht: 12. Dezember 2024
Gesehen am 07.03.2025